2014
DOI: 10.1108/jea-02-2013-0019
|View full text |Cite
|
Sign up to set email alerts
|

Finance equity, student achievement, and justice

Abstract: Purpose – The purpose of this paper is to explore the connections between state education finance distribution models and student achievement. To date, lawsuits challenging the constitutionality of state finance systems have been heard in 45 states; the judicial interpretation of the requirement to provide equality of educational opportunity has led to changes in finance distribution models as well as the implementation of accountability policy. Design/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Building on this work, Knoeppel, First, Della Sala, and Ordu (2014) investigated the particularities of the equity ratio in light of varying notions of equality of educational opportunity and judicial interpretations of states' constitutional language and adequacy-based finance litigation. They concluded that factors such as states' differing finance and accountability policy goals, interpretations of court decisions and equality of educational opportunity, definitions of proficiency, and finance and accountability policy coherence complicated explanations of the equity ratio.…”
Section: Measuring States' Progress Toward Equality Of Opportunitymentioning
confidence: 99%
See 2 more Smart Citations
“…Building on this work, Knoeppel, First, Della Sala, and Ordu (2014) investigated the particularities of the equity ratio in light of varying notions of equality of educational opportunity and judicial interpretations of states' constitutional language and adequacy-based finance litigation. They concluded that factors such as states' differing finance and accountability policy goals, interpretations of court decisions and equality of educational opportunity, definitions of proficiency, and finance and accountability policy coherence complicated explanations of the equity ratio.…”
Section: Measuring States' Progress Toward Equality Of Opportunitymentioning
confidence: 99%
“…In addition to the traditional finance measures used in this analysis, researchers developed and calculated a metric titled the "opportunity gap" to represent the degree of misalignment between the equity of states' education finance systems and the intended student performance outcomes of accountability policies. Because court decisions have often emphasized equality of inputs or outputs as sufficient to meet equality of educational opportunity (Knoeppel et al, 2014), the opportunity gap was created to represent either inequities in finance inputs, student performance outcomes, or a misalignment of both policies. Whereas current finance measures can be used to independently measure the equity of inputs and outputs, the opportunity gap was intended to measure the simultaneous equity of both and is represented as the difference between an ideal alignment of each state's finance inputs with student performance outputs and states' actual measures of finance and student performance.…”
Section: Opportunity Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…Adams ( 2009) and Knoeppel et al (2014) confirmed that a robust financial system is an essential component of a healthy education system.…”
Section: Chapter Summarymentioning
confidence: 99%